Environmental monitoring of atmospheric pollution in the Karaganda region - Nurlybayeva, K.A.; Mukasheva, G.Zh.; Sarsembaeva, A.Sch.; Kanafina, B.A. (Академик Е.А. Бөкетов атындағы Қарағанды университетінің баспасы, 2025)
Atmospheric air pollution is one of the most acute environmental problems of the Karaganda region, which is an industrially developed region of Kazakhstan. The intensive development of industry, especially mining and metallurgy, contributes to the release of significant amounts of pollutants into the atmosphere. To prevent negative consequences, regular environmental monitoring is necessary, which allows you to monitor the state of the environment and take measures to improve it. Karaganda region is one of the most industrially developed regions of Kazakhstan, which is accompanied by high levels of atmospheric pollution. Over the past 10 years, the air quality situation in the region has undergone both periods of improvement and exacerbation, due to various factors such as the introduction of purification technologies, industrial development and changing climatic conditions.
Keywords: environmental monitoring; atmospheric pollution; Karaganda region; air quality; environmental assessment